An Analysis of Policy Solutions to Mitigate the Impact of Greenhouse Gas Emissions and Increase Public Awareness and Participation - Chanmony, Mak (Journal of Public Representative and Society Provision, 2021)
This research analyzes policy solutions aimed at mitigating greenhouse gas emissions and enhancing public awareness and participation in climate action. By examining diverse policy interventions, such as renewable energy incentives, carbon pricing mechanisms, energy efficiency standards, afforestation, reforestation, and sustainable agricultural practices, the study evaluates their effectiveness, cost-effectiveness, equity, flexibility, and political feasibility. The analysis draws on both primary data from interviews with policymakers, environmental advocates, and community leaders, and secondary data from literature reviews. The findings reveal that renewable energy incentives and carbon pricing mechanisms are among the most effective strategies for reducing emissions, although their feasibility varies due to financial, political, and social factors. Public education and community-based approaches emerge as the most successful methods for increasing public awareness and fostering participation, especially when tailored to local contexts and combined with digital platforms to reach wider audiences. However, gaps in current policy frameworks remain, including insufficient integration of international cooperation, underrepresentation of marginalized communities, and limited focus on behavioral change and engagement strategies. This study highlights the importance of adopting a combination of policy measures that leverage the strengths of each intervention while addressing their limitations. It calls for more inclusive and integrated approaches that align local, national, and global policies, actively involve underrepresented communities, and promote behavioral changes through targeted interventions. By identifying these gaps and opportunities, the research provides actionable recommendations for policymakers, stakeholders, and civil society organizations to create more comprehensive, equitable, and effective climate strategies.